2008
DOI: 10.2172/939853
|View full text |Cite
|
Sign up to set email alerts
|

Sludge Batch 5 Simulant Flowsheet Studies

Abstract: The Defense Waste Processing Facility (DWPF) will transition from Sludge Batch 4 (SB4) processing to Sludge Batch 5 (SB5) processing in early fiscal year 2009. Tests were conducted using non-radioactive simulants of the expected SB5 composition to determine the impact of varying the acid stoichiometry during the Sludge Receipt and Adjustment Tank (SRAT) and Slurry Mix Evaporator (SME) processes. The work was conducted to meet the Technical Task Request (TTR) HLW/DWPF/TTR-2007-0007, Rev. 1 1 and followed the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…The pH profiles of the four SB6-A runs in general matched profiles noted during previous CPC simulations 14 . As shown in Figure 2, the pH was lower for runs with higher acid additions.…”
Section: Ph Profilessupporting
confidence: 77%
“…The pH profiles of the four SB6-A runs in general matched profiles noted during previous CPC simulations 14 . As shown in Figure 2, the pH was lower for runs with higher acid additions.…”
Section: Ph Profilessupporting
confidence: 77%
“…IC measurements of NH 4 + in the FAVC condensate, which is downstream of the scrubber and upstream of the Nafion dryer, showed negligible ammonium ion in the condensate despite the presence of large concentrations of NH 3 and NH 4 + , 925 ppm (just upstream of the scrubber) and 934 μg/mL (in scrubber solution), respectively; thus, it can be concluded that the ammonia scrubber worked efficiently.…”
Section: Process Sampling Results Sb6-25mentioning
confidence: 91%
“…Savannah River National Laboratory (SRNL) performed these supplemental runs as requested by Technical Task Request (TTR) 2 following the guidelines of a Task Technical and Quality Assurance Plan (TT&QAP) 4 . The R&D Directions are given in the notebook SRNL-NB-2010-00047.…”
Section: List Of Tablesmentioning
confidence: 99%
“…17 As shown in Figure 3-3 the pH of the runs was lower for runs with coal and little change in pH occurred during boiling in runs with coal. Formic acid decomposition during high acid, no coal runs resulted in a higher final pH.…”
Section: Srat Cycle Ph Profilesmentioning
confidence: 88%